Subak endurance in facing external development in South Bali, Indonesia - Sriartha, I Putu; Giyarsih, Sri Rum (International research journal of management, IT and social sciences, 2017)
The traditional Balinese irrigation system is managed by the traditional institution called subak. UNESCO has established subak as world cultural heritage that must be protected. The facts on the field showed the existence of subak is increasing threatened along with its external environment development. This research aims at analyzing the spatial patterns of subak Tri Hita Karana (THK) endurance and external symptoms that threaten it. The research was conducted in 69 existing subak in Badung Regency, South Bali Province. The data about THK endurance were collected from subak leaders using interview technique, field observations, and document collecting. They were analyzed using quantitative descriptive technique and spatial analysis using geographical information system (GIS). The results showed that THK endurance in the subak system fell under three categories: high (29 subak), medium (28 subak) and low (12 subak). Spatially, each category forms a cluster pattern following the principle of distance decay, related to the dynamic development of its external environment. The external development that threatens THK endurance, i.e.: change in the region’s spatial planning from the government, development in the non-agricultural economic sector, (3) population development and built-up areas, and development of road infrastructure.